Material Thermal Characteristic Analysis and Experimental Research of the AMT Clutch Friction Pair - Long Meiyuan; Zhang Zhigang; Shi Xiaohui; Chen Yanyun; Qin Tian (Jixie chuandong)
According to the special structural forms of AMT clutch,in order to get the temperature rise characteristics of clutch friction with different material parameters under Specific conditions. Firstly,the 3D model of pressure plate and friction plates are established,the heat transfer physical model of AMT clutch is analyzed,the thermal boundary conditions of clutch is determined. Then,by using the software of ANSYS,the transient temperature field of pressure plate and friction plates are simulate,and the temperature rising curve is got. Finally,the simulation result of finite element analysis is verified through the AMT clutch comprehensive performance test bench. The results have important significance for AMT clutch structural optimization design and material selection.